EVALUATION OF THE IMPLEMENTATION OF LEARNING OUTCOME TESTS IN PAI-BP LEARNING IN CLASS VI OF SDN 5 MENTENG PALANGKA RAYA - Ihsan Auliya Arrasyid Arrasyid; Abdul Qodir; Aghnaita Aghnaita (MADINASIKA, 2026)
This study aims to evaluate the implementation of Islamic Religious Education and Morality (PAI-BP) learning outcome tests in grade VI of SDN 5 Menteng Palangka Raya using the CIPP (Context, Input, Process, Product) evaluation model with a quantitative approach. This study is an evaluative study with grade VI students as subjects, who were selected purposively. Data collection was conducted through a four-point Likert scale questionnaire, observation using a checklist, and documentation, then analyzed descriptively and quantitatively. The results showed that the implementation of the PAI-BP learning outcome test in the context aspect obtained an average questionnaire score of 3.36 in the “High” category and an observation score of 3.20 in the “Good” category. The input aspect obtained an average questionnaire score of 3.37, categorized as “High,” and an observation score of 3.89, categorized as “Very Good.” The process aspect showed an average questionnaire score of 3.34, categorized as “High,” and an observation score of 3.60, categorized as “Very Good.” The product aspect obtained an average score of 3.39, categorized as “High,” and an observation score of 2.89, categorized as “Good.” The CIPP model effectively provides a comprehensive overview as a basis for improving learning evaluation.